The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Design and Verification of Microprocessor Systems for High-Assurance Applications 2010
DOI: 10.1007/978-1-4419-1539-9_12
|View full text |Cite
|
Sign up to set email alerts
|

Specification and Checking of Software Contracts for Conditional Information Flow

Abstract: Abstract. Information assurance applications built according to the MILS (Multiple Independent Levels of Security) architecture often contain information flow policies that are conditional in the sense that data is allowed to flow between system components only when the system satisfies certain state predicates. However, existing specification and verification environments, such as SPARK Ada, used to develop MILS applications can only capture unconditional information flows. Motivated by the need to better for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Many of the minimization steps can be implemented using simple syntactic checks, and we are in the process of implementing and proving correct a minimizer in Coq that will allow us to dramatically reduce the number of SMT solver calls. Experimental results from our earlier work [1] in which we used only syntactic scans to minimize showed that inference for almost all the procedures could be completed in less than a second. Our approach is compositional which greatly aids scalability when considering the overall time requirements for a complete application.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many of the minimization steps can be implemented using simple syntactic checks, and we are in the process of implementing and proving correct a minimizer in Coq that will allow us to dramatically reduce the number of SMT solver calls. Experimental results from our earlier work [1] in which we used only syntactic scans to minimize showed that inference for almost all the procedures could be completed in less than a second. Our approach is compositional which greatly aids scalability when considering the overall time requirements for a complete application.…”
Section: Discussionmentioning
confidence: 99%
“…In [1] that approach was applied to the (heap-free) SPARK setting and worked out extensively, with an algorithm for computing loop invariants and with reports from an implementation; then arrays were handled in subsequent work [2].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations